2016
DOI: 10.1002/jobm.201600175
|View full text |Cite
|
Sign up to set email alerts
|

Crataeva nurvala nanoparticles inhibit virulence factors and biofilm formation in clinical isolates of Pseudomonas aeruginosa

Abstract: Green synthesized nanoparticles have gained great attention due to their non-toxic and non-hazardous nature. In the present study, bark extract of the medicinal plant in Ayurveda Crataeva nurvala (Buch-Ham) (CN) was chosen for the biosynthesis of silver nanoparticles (AgNPs). These NPs were characterized by Ultra violet visible spectroscopy, Fourier Transform Infra Red, Atomic Force Microscopy, and Transmission Electron Microscopy (TEM). The average particle size of green synthesized CN-AgNPs was 15.2 ± 1.01 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 47 publications
5
30
0
Order By: Relevance
“…Internalization of mycofabricated AgNPs and their effects on QS-operated virulence factors were reported. Ali et al [20] also reported similar findings where AgNPs inhibited QS-mediated virulence factors. Our SEM analysis results agreed with previous findings of Samantha et al [42].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Internalization of mycofabricated AgNPs and their effects on QS-operated virulence factors were reported. Ali et al [20] also reported similar findings where AgNPs inhibited QS-mediated virulence factors. Our SEM analysis results agreed with previous findings of Samantha et al [42].…”
Section: Discussionmentioning
confidence: 59%
“…Complex bonds formed due to the interaction between biomolecules present in the extract and gold particles were analyzed by FTIR (PerkinElmer, CT, USA) spectroscopy in the range of 4000-400 cm −1 at room temperature. The adsorption spectrum displayed different peaks, which corresponded to the various bonds formed [20].…”
Section: Ftir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 The lysis efficacy of human red blood cells by C. albicans after treatment with varying concentration of ScAgNPs was analyzed as previously described methods with some modification. 7,30 Further, the effect of ScAgNPs on the germ tube formation by C. albicans was examined as a method previously reported with some modification. 24 Effect of ScAgNPs on C. albicans biofilm The effects of different concentration of ScAgNPs on C. albicans biofilm were assessed by Congo Red Agar method (qualitatively), as described in our previous study with slight modification.…”
Section: Effect Of Scagnps On Virulence Factors Of Candida Sppmentioning
confidence: 99%
“…The antimicrobial activity of biogenic AgNPs was well documented in the literature. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] However, there are very few studies available in the literature on the inhibition of production of various extracellular hydrolytic enzymes and germ tubes in Candida spp by nanoparticles. [22][23][24] Due to the scarcity in the literature on the inhibition of production of various virulence factors by Candida spp, herein for the first time we have reported the potent inhibitory effects of green synthesized AgNPs on the production of different virulence attributes of Candida species isolated from oropharyngeal mucosa of HIV patients.…”
Section: Introductionmentioning
confidence: 99%